Monetary Policy, Rule-of-Thumb Consumers and External Habits: A G7 Comparison - Giovanni Di Bartolomeo; Lorenza Rossi; Massimiliano Tancioni (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2009)
This paper extends the standard New Keynesian dynamic stochastic general equilibrium (DSGE) model to agents who cannot smooth consumption (i.e. spenders) and are affected by external consumption habits. Although these assumptions are not new, their joint consideration strongly affects some theoretical and empirical results addressed by the recent literature. By deriving closed-form solutions, we identify different demand regimes and show that they are characterized by specific features regarding dynamic stability and monetary policy effectiveness. We also evaluate our model by stochastic simulations obtained from the Bayesian parameters estimates for the G7 economies. From posterior impulse responses we address the empirical relevance of the different regimes and provide comparative evidence on the heterogeneity of monetary policy effects among countries.
Keywords: E61; E63; 330; Rule-of-thumb; habits; monetary policy transmission; determinacy; New Keynesian DSGE model; monetary policy; Monte Carlo Bayesian estimators